P283 Chronic Obstructive Pulmonary Disease (copd) Case-finding And Tobacco Dependence On Long Stay Psychiatric Wards. (10th November 2014) - Hughes, D; Jeanneret, M; Johansson, F; Sherring, K; Restrick, L
Abstract : Introduction and objectives: 42% of UK tobacco smoked is consumed by people with mental disorders. 1 Smoking prevalence, and the proportion of highly-dependent smokers, are increased in patients with severe mental illness (SMI) and smoking is the main cause of high premature mortality in this group. 1 The prevalence of COPD, a disease with >85% smoking-attributable deaths, in psychiatric in-patients is unknown and patients with SMI are less likely to have physical-health-checks and treatment. 1 We hypothesised that COPD is under-diagnosed and under-treated in in-patients with SMI. Methods: Case notes review and a structured smoking/respiratory assessment, using NICE COPD guidance with spirometry/oximetry, 2 were performed for in-patients with SMI over 1 month on three long-term psychiatric wards in an inner-city mental health trust. Results: Patient demographics are shown in the Table. 34/41 (83%) were confirmed current tobacco smokers with mean (SD) 34 (28) pack-years; 5 were non-smokers and 2 ex-smokers. 24/41 (59%) were previous/current cannabis smokers. Quit Smoking Support (QSS) was offered to 25/34 (74%) tobacco smokers with medication prescribed for 9/34 (26%). Median (range) self-assessed MRC-breathlessness score was 1 (1–2); (n = 16 and 18 did not engage). Mean (SD) oxygen saturation was 96.6 (2.4)% (n = 21; 13 did not engage). Three smokers (9%) had an existing diagnosis of COPD. 18/28 eligible patients had spirometry; 10 (36%) did not engage. Mean (SD) FEV1 was 2.41 (1.01) L; 4 /18 (22%) were obstructive. 3/6 (50%) smokers with COPD (1 ex-smoker) were offered QSS and 2 were referred for respiratory input. Conclusions: COPD prevalence was 17% in this in-patient group, over half of whom were undiagnosed. A third of patients declined spirometry, reflecting challenges of engagement in SMI. Nevertheless 2 in 9 tests resulted in new COPD diagnoses. Smoking prevalence was high at 83% but 1 in 5 smokers were not offered QSS, including half of those with COPD. These results support the case for respiratory-mental health collaborations during long psychiatric admissions. References: No health without mental health. Department of Health. 2011 NICE clinical guideline 101. Chronic obstructive pulmonary disease. 2010